2000
DOI: 10.1093/pcp/pcd008
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Waxy Genes with Highly Active Promoters Effectively Suppress Waxy Gene Expression in Transgenic Rice

Abstract: ;To regulate Waxy (Wx) gene expression by introducing antisense genes, we connected the 2.3 kb Wx cDNA having 450 bp of the Wx first intron in reverse orientation to rice Wx and maize alcohol dehydrogenase1 (Adh1) promoters and used these constructs to transform rice plants. Of 10 independent transgenic lines analysed, four lines showed various degrees of reduction in amylose and WAXY (WX) protein levels in the endosperm. In two transgenic lines, complete absence of amylose was observed which made the seeds op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The first is to suppress GBSS activity. Expression of antisense GBSSI has been reported to yield a rice starch with reduced AC Itoh et al 1997;Terada et al 2000). The second mechanism is through modulation of GBSSI promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…The first is to suppress GBSS activity. Expression of antisense GBSSI has been reported to yield a rice starch with reduced AC Itoh et al 1997;Terada et al 2000). The second mechanism is through modulation of GBSSI promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have found that mutations at other loci, such as du-1 and du-2, also cause a reduced amylose content through their effects on the splicing of the waxy pre-mRNA , and that complete absence of amylose or its reduction was observed in transgenic rice whose wild-type wx gene expression was suppressed by antisense genes (Terada et al 2000). These studies indicate that a variety of mechanisms are responsible for the waxy expression, including transcriptional and post-transcriptional processing, and translational regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the introduction of the antisense Wx gene into Japonica rice causes a reduction of amylose in the endosperm (Shimada et al 1993, Terada et al 2000. These studies showed that the differential regulation of the antisense gene expression by using low-or high-active promoters led to various levels of suppression of the endogenous Wx gene expression.…”
Section: Introductionmentioning
confidence: 99%